Tattooing in Adolescent: Between Narcissism, Acting out and Alexithymia - Mohand, Samir; Ismaili, Yamna (Milev Journal of Research and Studies, 2021)
This article is a study psychological of tattoo language at adolescence, and concluded that is an intimate symbolic experience in the teenager expresses his own feelings and identity. Moreover a desire to achieve his excellence, and repair of the containing function of the skin, and as guaranteeing a delimitation inside/ outside, it carries a narcissistic and erotic value in the body for the first subjects. Accompanied by acting out in the face of conflicts, with a state of alexithymia, as a psychological defense against pain